Tópicos de geometria plana, analítica e esférica através de uma sequência de atividades - Ribeiro, Rafael Silva (2015)
This work suggests a sequence of complementares activities to geometry. The plan euclidian geometry activities to make use of ruler, compass, transferor, cellphone and also the dynamic geometry software Geogebra. Additionally, to analytic geometry, we suggest activities of some de?nitions and properties of cartesian plan and vectors. In espheric geometry, the activities are related to the distance between two points and areas in the surface of our planet. The principal object is trazer both the teachers and students a qualitative increase in the learning of geometry.